An investigation into the flight dynamics of airships with application to the YEZ-2A - Gomes, S. B. V. (Cranfield University, 1990)
In order to construct a flight dynamics computer simulation model of airship flight with a high degree of fidelity in the aerodynamic modelling, extensive wind tunnel testing was carried out. This was aimed at, first developing some specific airship wind tunnel testing techniques and then to obtain aerodynamic data for the YEZ-2A project airship being designed and built by Airship Industries for the US Navy. The wind tunnel testing techniques so developed insured a good matching between wind tunnel results and flight test data from existing airships. The next step consisted in the construction of the flight dynamics computer simulation model. This was a full six-degree-of-freedom (6 DOF) non-linear model written in the simulation language ACSL, and the wind tunnel generated data for the YEZ-2A airship provided the aerodynamic data base. The computer simulation model was then used to study the YEZ-2A aerodynamic stability modes, to obtain a catalogue of vehicle responses to both aerodynamic and power control inputs and finally to predict some of its longitudinal handling qualities characteristics.